LECTURES IN MEDICAL EDUCATION: STUDENTS’ VIEWS - Manzoor, Iram; Mumtaz, Aneeqa; Habib, Marriam; Tariq, Sana; Elahee, Mahreen; Javaid, Iram (Journal of Ayub Medical College Abbottabad, 2011)
Background: Lectures are considered most effective mode of information transfer amongst teachers and students in medical education, but in recent years there has been a noticeable decline in the attendance of lectures. Our objective was to assess the reasons of medical students’ disinterest in lectures. Methods: A cross-sectional survey was conducted in Department of Community Medicine, Fatima Memorial College of Medicine and Dentistry from December 2010 to June 2011. A non-probability technique of consecutive sampling was used to collect 307 participants from all five years of MBBS. Reasons of disinterest of medical students were asked in the questionnaire. The data was analysed on SPSS-17, Chi square test was applied and p-value was fixed at ‰¤0.05 as significant. Results: Factors affecting the lecture attendance of these medical students include distance of residence from the college 215 (70%), strictness of teacher in marking attendance 227 (73.9%), interest in subject 216 (70.4%), subject is part of examination 257 (83.7%), and university requirement 249 (81.1%). The personality traits of teacher affecting attendance of medical students in lectures include good communication 216 (70.4%), command on subject 194 (63.2%), students’ interaction in class 180 (58.6%), friendly attitude 202 (65.8%), good control on class 163 (53.1%), punctuality 100 (32.6%), sense of humour 160 (52.1%), and humane behaviour 135 (44%). Conclusion: The interest of medical students can be enhanced and better attendance achieved with slight modifications in identified reasons. Keywords: Medical students, Attendance, Lectures, Medical Education